IoT for health-based system: analog network coding with energy harvesting - Dalal Abdulmohsin Hammood; Mahmoud Shuker Mahmoud; Ahmed Alkhayyat (Institute of Advanced Engineering and Science, 2020)
In the recent health-care field, the interent of health thigs (IoHT) technologies provide appropriateness between doctors and people receiving medical treatment, because they are useful to several curative domains. The wireless body sensors networks which can be abbrivated as every technology of a WBSN is an important one from IoT growing’s of the health-care model, as all sick people are observed utilizing some set of nodes of sensors that are light as well as with no high power. In this paper, we proposed energy harvesting-based inter-WBSN cooperation network coding (EH-IWCNC) for Internet of Medical Things.